Socio-economic differentials in disability among older people in Sri Lanka - Malsha, R.L.R. (University of Colombo, 2017)
Research in ageing and disability has shown that people of lower socio-economic status experience more difficulties as they grow older than do those of higher socioeconomic status. However, in Sri Lanka, it is rare to find investigations into disability in old age carried out by such differentials. This study examines socio-economic status and disability among older people in Sri Lanka, using secondary data from the Population and Housing Census, 2012, around six domains of disability such as seeing, hearing, walking, cognition, self-care and communication. The results indicate that females report a higher proportion of disabilities than their male counterparts. Though Sri Lankan females experience a higher life expectancy (79 years) than males (72 years), females tend to live longer with difficulties as they grow older, which can have a significant impact on their health and well-being. The results also revealed that disability persists among middle-old and the oldest-old groups. The majority of the oldest-old people experience disability in walking (44.6%), seeing (38.7%), hearing (33.1%), and cognition (25.7%). The highest proportion of females with disabilities (62%) has been reported from the urban sector, while the highest proportion of males with disabilities (43.6%) has been reported from the estate sector. Among demographic and socio-economic factors, age, gender, employment participation, marital status, and level of education show a significant relationship with the disability status of older people in Sri Lanka. These findings suggest that policies and programmes need to focus on improving health infrastructure and geriatric health care facilities to support older people who have difficulties.
Keywords: older population, ageing, disability, differentials in difficulty